The Evolution of Interventional Cardiology - Parry, Nicola (MD Conference Express, 2014)
Interventional cardiology had its beginnings in Andreas Gruentzig’s (1939–1985) dream to “accomplish catheter-based percutaneous treatment of vascular disease in alert, awake patients” [Sievert H et al., eds. Percutaneous Interventions for Congenital Heart Disease. USA: CRC Press; 2007:29]. This article provides an overview of the advances in interventional cardiology that have occurred since Prof. Gruentzig performed the first balloon angioplasty in 1977 using a self-made catheter.